Managing land use and land cover change in the biodiversity context with regard to efficiency, equality and ecological effectiveness - Cornelia Ohl; Martin Drechsler; Karin Johst; Frank Wätzold (UFZ-Umweltforschungszentrum Leipzig-Halle, 2006)
The introduction of conservation-friendly farming measures is an important tool for biodiversity conservation. Recently, a debate has started whether this money is spent effectively, i.e. whether it successfully contributes to conserve biodiversity in agricultural landscapes. Several types of criticism have been raised that are adequately responded by environmental policies leading to spatially and temporally heterogeneous habitats. However existing policies for species conservation are still designed to support one conservation measure only by paying an equal amount of compensation to all land-users carrying out the corresponding measure. Regarding ecological findings we firstly point out in which cases environmental policies have to be differentiated in space and time. Secondly, we analyse the necessary and sufficient conditions for transfer schemes to exist that are able to introduce a spatio-temporally heterogeneous land use and land cover type. Thirdly, we reveal that strategic considerations of land-owners limit efficiency and fairness considerations of the policy makers when determining the ecologically accurate payment scheme. However ' surprisingly ' if policy makers seek to minimise their budget required for implementing the desired policy goal, this at the same time guarantees that the individual profits of the land-owners (when performing with the desired policy goal) are as equal as feasible.
Keywords: 330